Tinjauan Etnozoologi Terkait Larangan Penyembelihan Sapi (Bos taurus) di Kudus Menurut Filosofi Ajaran Sunan Kudus - Adillah, Dzuhrotin; Banati, Olivia; Fashihah, Anna Bariroh; Nada, Shofwatun (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The study of ethnozoology is closely related to local culture and knowledge and their interaction with the surrounding environment. Islam was brought to Kudus by Ja’far Shadiq, known as Sunan Kudus, using a unique da’wah strategy, namely, the fatwa on the prohibition of cow slaughter for the people of Kudus. The social tradition of the community regarding the prohibition of slaughtering cattle, makes the Kudus area more likely to consume buffalo meat than beef. The purpose of this research is to find out the ethnozoological perspective related to the prohibition of cattle slaughter (Bos taurus) according to the philosophy of the teachings of Sunan Kudus in socio-cultural and economic life. The research method used is qualitative field research with qualitative description analysis techniques. Data collection was conducted through observation, literature review and interview results related to general knowledge of customary, cultural and ethnozoological aspects in depth with informants. The data were analyzed descriptively qualitatively by making transcripts of the interview results which were written carefully taking and recording important information with the research context. The research was conducted in several areas of Kudus, including Kirig Village, Ngembalrejo Village, and Dawe District. Based on the results of the research, the fatwa on the prohibition of slaughtering cows in Kudus has been believed by the community from the past until now, but the results show that there are still some Kudus people who slaughter cows, one of which is the Muhammadiyah Islamic group, besides that, the Kudus community utilizes buffaloes as a function of cows, all of which go back to their respective beliefs because there are still many cattle breeders found to be traded.